A negative electrode material and preparation method thereof and sodium ion battery

By using plastic and zinc salt to prepare a three-dimensional carbon frame negative electrode material, the problem of low specific capacity of sodium ion batteries is solved, and excellent rate performance, long cycle stability and high discharge specific capacity are achieved.

CN118545694BActive Publication Date: 2025-04-11SUZHOU DERBY ELECTRONIC MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410462946.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-17
Publication Date
2025-04-11
Estimated Expiration
2044-04-17

AI Technical Summary

Technical Problem

The specific capacity of existing sodium ion batteries is relatively low, which makes it more difficult to freely deintercalate sodium ions in the negative electrode material.

Method used

Plastics are used as the carbon source and zinc salts are used as pore-forming agents to prepare a three-dimensional carbon skeleton negative electrode material loaded with porous carbon nanosheets to improve the intercalation and deintercalation efficiency of sodium ions.

Benefits of technology

The specific capacity of sodium ion batteries is significantly improved, rate performance, long cycle stability and discharge specific capacity are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118545694B_ABST
    Figure CN118545694B_ABST
Patent Text Reader

Abstract

The present invention provides a negative electrode material and a preparation method thereof and a sodium ion battery, and relates to the field of electrochemical energy storage technology. The preparation method comprises the following steps: S1: dissolving a zinc salt in an organic solvent to obtain a zinc salt solution; S2: placing a plastic in the zinc salt solution, condensing and refluxing at 80-200°C to obtain a reaction solution; S3: after the reaction solution is cooled to room temperature, it is placed in an inert gas atmosphere, and pyrolyzed at 500-1200°C to obtain a negative electrode material. The preparation method of the negative electrode material provided by the present invention uses plastic as a carbon source and a zinc salt as a pore-forming agent, and obtains a three-dimensional carbon skeleton negative electrode material loaded with porous carbon nanosheets by condensation reflux dissolution and liquid carbonization, and the negative electrode material exhibits excellent rate performance, outstanding long cycle stability and high discharge specific capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a negative electrode material and a preparation method thereof, and a sodium ion battery. Background Art

[0002] Among the numerous energy storage devices, sodium-ion batteries stand out because of the abundant storage of sodium in the earth's crust (Na: 2.8 wt %, Li: 0.0017 wt %), easy availability, and low production cost. Currently, sodium-ion batteries have become the most promising candidate to replace lithium-ion batteries as large-scale electrical energy storage devices.

[0003] However, due to the large radius of sodium ions, it is difficult for sodium ions to freely embed and deintercalate in the negative electrode material during the charging and discharging process, resulting in a low specific capacity of sodium ion batteries.

[0004] In view of this, how to obtain carbon materials suitable for sodium ion embedding / de-embedding is a technical problem that needs to be solved urgently. Summary of the invention

[0005] In order to solve the problem of low specific capacity of sodium ion batteries in the prior art, the present invention provides a method for preparing a negative electrode material. The preparation method uses plastic as a raw material, and obtains a three-dimensional carbon skeleton negative electrode material with a porous structure through condensation reflux dissolution and liquid carbonization, which is helpful for sodium ion deintercalation, thereby helping to improve the specific capacity of the sodium ion battery, solving the problem of low specific capacity of the sodium ion battery in the prior art.

[0006] The technical solution adopted by the present invention to solve the technical problem is:

[0007] A method for preparing a negative electrode material comprises the following steps:

[0008] S1: dissolving a zinc salt in an organic solvent to obtain a zinc salt solution;

[0009] S2: placing the plastic in the zinc salt solution, condensing and refluxing at 80-200° C. to obtain a reaction solution;

[0010] S3: After the reaction solution is cooled to room temperature, it is placed in an inert gas atmosphere and pyrolyzed at 500-1200° C. to obtain a negative electrode material.

[0011] Optionally, the plastic is polyethylene terephthalate.

[0012] Optionally, the plastic is waste polyethylene terephthalate.

[0013] Optionally, the zinc salt is selected from at least one of anhydrous zinc acetate, zinc chloride, and zinc nitrate hexahydrate.

[0014] Optionally, the zinc salt is selected from anhydrous zinc acetate.

[0015] Optionally, the organic solvent is selected from at least one of DMF, DMA, DMSO and THF.

[0016] Optionally, the organic solvent is DMF.

[0017] Optionally, the usage ratio of the zinc salt, the organic solvent and the plastic is (50-400) mg: (10-100) mL: (0.1-4) g.

[0018] Optionally, the condensation reflux time in step S2 is 4-20 hours.

[0019] Optionally, the pyrolysis time in step S3 is 2-8 hours.

[0020] Optionally, the pyrolysis rate in step S3 is 2-10°C min -1 .

[0021] Another object of the present invention is to provide a negative electrode material, which is prepared by the negative electrode material preparation method as described above.

[0022] Another object of the present invention is to provide a sodium ion battery comprising the negative electrode material as described above.

[0023] The beneficial effects of the present invention are:

[0024] The preparation method of the negative electrode material provided by the present invention uses plastic as a carbon source and zinc salt as a pore-forming agent, and obtains a three-dimensional carbon skeleton negative electrode material loaded with porous carbon nanosheets through condensation reflux dissolution and liquid carbonization. The negative electrode material exhibits excellent rate performance, outstanding long cycle stability and high discharge specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0026] Figure 1 These are scanning electron microscope (SEM) images and transmission electron microscope (TEM) images of PCN@3DC-2 obtained in the preparation process of Example 2 of the present invention; wherein (a~c) are SEM images, and (d~f) are TEM images;

[0027] Figure 2 These are the high-resolution transmission electron microscopy (HRTEM) images, selected area electron diffraction (SAED) images, and elemental mapping (EDS) images of PCN@3DC-2 obtained in the preparation process of Example 2 of the present invention; wherein (a and b) are HRTEM images, (c) is a SAED image, and (d~h) are EDS images;

[0028] Figure 3 These are SEM images and TEM images of PC-1 obtained in the preparation process of Comparative Example 1 of the present invention; wherein (a-c) are SEM images, and (d-f) are TEM images;

[0029] Figure 4 These are SEM images and TEM images of PC-2 obtained in the preparation process of Comparative Example 2 of the present invention; wherein (a-c) are SEM images, and (d-f) are TEM images;

[0030] Figure 5 These are SEM images and TEM images of PC-3 obtained in the preparation process of Comparative Example 3 of the present invention; wherein (a~c) are SEM images, and (d~f) are TEM images;

[0031] Figure 6 The N2 adsorption-desorption isotherms and pore size distribution diagrams of PCN@3DC-2 obtained in the preparation process of Example 2 of the present invention are shown in FIG. 1 , wherein (a) is a N2 adsorption-desorption isotherm diagram, and (b) is a pore size distribution diagram;

[0032] Figure 7 The Raman spectra, X-ray powder diffraction (XRD) spectra of PCN@3DC-2 obtained in the preparation process of Example 2 of the present invention and PC-1, PC-2 and PC-3 prepared in Comparative Examples 1 to 3, and the X-ray photoelectron spectrum (XPS) of PCN@3DC-2 prepared in Example 2; wherein (a) is a Raman spectrum, (b) is an XRD spectrum, (c) is an XPS full spectrum, (d) is a C 1s XPS spectrum, (e) is a N 1s XPS spectrum, and (f) is an O 1s XPS spectrum;

[0033] Figure 8 The PCN@3DC-2 prepared in Example 2 of the present invention has a 0.1 mV s -1 Cyclic voltammetry (CV) diagrams of PCN@3DC-1, PCN@3DC-2, PCN@3DC-3, PC-1, PC-2 and PC-3 at different current densities and the rate performance diagrams at 0.1 A∙g -1 The long cycle performance of PCN@3DC-2 at current density of 1 A∙g -1 and 5 A∙g -1 Long cycle performance diagram at current density of 0.1 A∙g -1 Long cycle performance diagram at current density of 1 A∙g -1 The long cycle performance at a current density of 5 A∙g is shown in (d). -1 (e) is the long cycle performance diagram at a current density of , and (e) is the rate performance diagram. DETAILED DESCRIPTION

[0034] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0035] In order to solve the problem of low specific capacity of sodium ion batteries in the prior art, the present invention provides a method for preparing a negative electrode material, the preparation method comprising the following steps:

[0036] S1: dissolving a zinc salt in an organic solvent to obtain a zinc salt solution;

[0037] S2: placing the plastic in a zinc salt solution, and condensing and refluxing at 80-200° C., preferably 155° C., to obtain a reaction solution;

[0038] S3: After the reaction solution is cooled to room temperature, it is placed in an inert gas atmosphere and pyrolyzed at 500-1200° C., preferably 900° C., to obtain a negative electrode material.

[0039] Among them, the plastic, as a precursor of the carbon skeleton, is placed in a zinc salt solution composed of zinc salt and an organic solvent, and then condensed and refluxed. Under the action of the organic solvent, the plastic can be fully dissolved and fully mixed with the zinc salt; the obtained reaction solution is then cooled to room temperature and pyrolyzed; during the pyrolysis process, the plastic is re-crosslinked and carbonized, and the zinc salt, as a pore-forming agent, forms a large number of evenly distributed mesopores in the carbonized product through zinc sublimation, forming a three-dimensional framework material formed by crosslinking the carbon skeleton loaded with porous carbon nanosheets, so that the obtained carbon material is more suitable for the embedding and de-embedding of sodium ions, which helps to improve the specific capacity of the sodium ion battery; at the same time, the presence of the organic solvent also helps to introduce a large number of heteroatoms into the carbonized product and form macropores, which helps to further improve the electrochemical performance of the negative electrode material.

[0040] The negative electrode material obtained by the preparation method is a three-dimensional carbon skeleton structure formed by cross-linking the carbon skeleton of the loaded porous carbon nanosheet, and the present invention names it PCN@3DC-2, wherein PCN represents the porous carbon nanosheet and 3DC represents the three-dimensional carbon skeleton. The present invention obtains the target product PCN@C by condensation reflux dissolution and liquid carbonization, and the operation is simple and easy to implement.

[0041] Specifically, during the pyrolysis process of the present invention, the state of the pyrolysis precursor can be solid or liquid; the present invention preferably uses a liquid pyrolysis precursor; due to the large radius of sodium ions, the electrode material will undergo a more dramatic volume expansion phenomenon compared to lithium-ion batteries during the charge and discharge process, and will face slower kinetic problems, resulting in a decrease in the cycle stability and rate performance of sodium-ion batteries. The present invention first dissolves the plastic in an organic solvent through condensation reflux, and uses a liquid precursor for pyrolysis, so that the prepared negative electrode material is more suitable for sodium ion insertion / extraction, and has more excellent mechanical properties, thereby helping to alleviate the volume expansion during the charge and discharge process, and helping to give sodium-ion batteries excellent cycle stability and rate performance.

[0042] The preparation method of the negative electrode material provided by the present invention uses plastic as a carbon source and zinc salt as a pore-forming agent, and obtains a three-dimensional carbon skeleton negative electrode material loaded with porous carbon nanosheets through condensation reflux dissolution and liquid carbonization. The negative electrode material exhibits excellent rate performance, outstanding long cycle stability and high discharge specific capacity.

[0043] The preferred plastic of the present invention is polyethylene terephthalate (PET), and the high carbon content in the PET structure is utilized to ensure the electrochemical performance of the prepared negative electrode material.

[0044] In order to further reduce costs and realize the recycling of waste PET, the preferred plastic of the present invention is waste polyethylene terephthalate (PET).

[0045] Among them, polyethylene terephthalate (PET) is a plastic widely used in packaging and textiles, with an annual production scale of about 80.9 million tons in 2021. Unfortunately, only a small part (about 30%) of waste PET is currently recycled, and the recycling method is mainly through mechanical methods, and incineration and landfill are still the most popular treatment methods in countries around the world. However, due to the very stable chemical properties of PET, these waste PETs take at least 450 years to be completely degraded. Therefore, based on environmental and health issues, the conventional treatment of PET waste is unsustainable, and effective measures should be taken to reduce the pollution of waste PET to the environment and reduce the waste of resources by changing the recycling and treatment routes of waste PET. Due to the high carbon content in the PET structure, the present invention develops carbon-based materials from waste PET, while reducing costs, to achieve the recycling of waste PET to solve energy and environmental problems.

[0046] The raw materials used in the invention are low in cost, the preparation method is simple, and the invention has the advantages of being environmentally friendly and sustainable.

[0047] At present, most of the hard carbons are prepared as the negative electrode materials of sodium ion batteries using various biomass carbons as precursors, but the high cost of biomass carbons limits its large-scale production. Therefore, using waste PET with lower cost as raw materials and obtaining carbon materials suitable for sodium ion embedding / de-embedding through simple synthesis steps has a broader application prospect.

[0048] In the present invention, the zinc salt is preferably selected from at least one of anhydrous zinc acetate, zinc chloride, and zinc nitrate hexahydrate. During the pyrolysis process, Zn metal will sublime, resulting in the formation of a large number of mesopores in the carbonized product.

[0049] The present invention further prefers that the zinc salt is anhydrous zinc acetate.

[0050] The preferred organic solvent of the present invention is at least one selected from DMF, DMA, DMSO, and THF, and the organic solvent is further preferably DMF. On the one hand, it can dissolve the waste PET well under high-temperature condensation reflux. On the other hand, in combination with the present invention, the liquid precursor is used for pyrolysis. During the pyrolysis process, DMF can not only introduce a large number of N atoms into the product as a N source, but also form macropores in the product.

[0051] In order to take into account both the electrochemical performance and economic efficiency of the negative electrode material, the present invention preferably uses a ratio of zinc salt, organic solvent, and plastic of (50-400) mg: (10-100) mL: (0.1-4) g, and more preferably 170 mg: 30 mL: 1 g; the condensation reflux time in step S2 is preferably 4-20 h, and more preferably 12 h; the pyrolysis time in step S3 is preferably 2-8 h, and more preferably 6 h; the pyrolysis rate in step S3 is preferably 2-10 ° C min -1 , more preferably 5℃ min -1 .

[0052] Another object of the present invention is to provide a negative electrode material, which is prepared by the negative electrode material preparation method as described above.

[0053] The negative electrode material provided by the present invention uses plastic as a carbon source and zinc salt as a pore-forming agent, and obtains a three-dimensional carbon skeleton negative electrode material loaded with porous carbon nanosheets through condensation reflux dissolution and liquid carbonization. The negative electrode material exhibits excellent rate performance, outstanding long cycle stability and high discharge specific capacity.

[0054] Another object of the present invention is to provide a sodium ion battery, which comprises the negative electrode material as described above.

[0055] The sodium ion battery provided by the present invention uses plastic as a carbon source and zinc salt as a pore-forming agent as a negative electrode material, and obtains a three-dimensional carbon skeleton negative electrode material loaded with porous carbon nanosheets through condensation reflux dissolution and liquid carbonization, so that the sodium ion battery exhibits excellent rate performance, outstanding long cycle stability and high discharge specific capacity.

[0056] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0057] Example 1

[0058] This embodiment provides a method for preparing a negative electrode material, comprising the following steps:

[0059] S1: Dissolve 50 mg of anhydrous zinc acetate in 10 mL of DMF by ultrasonication to obtain a zinc salt solution;

[0060] S2: Wash the discarded coke bottles (waste PET) and cut them into small pieces, take 0.1 g of the coke bottle pieces and put them into a zinc salt solution, condense and reflux at 80°C and stir for 20 hours to obtain a reaction solution;

[0061] S3: After the reaction solution was cooled to room temperature, it was placed in a tube furnace under an Ar atmosphere at 2 °C min -1 The heating rate was set at 500 °C for 8 h to obtain PCN@3DC-1, the negative electrode material.

[0062] Example 2

[0063] This embodiment provides a method for preparing a negative electrode material, comprising the following steps:

[0064] S1: Dissolve 170 mg of anhydrous zinc acetate in 30 mL of DMF by ultrasonication to obtain a zinc salt solution;

[0065] S2: Wash and cut the discarded coke bottles (waste PET) into small pieces, take 1g of the coke bottle pieces and place them in a zinc salt solution, condense and reflux at 155℃ and stir for 12 h to obtain a reaction solution;

[0066] S3: After the reaction solution was cooled to room temperature, it was placed in a tube furnace under an Ar atmosphere at 5 °C min -1 The heating rate was set at 900 °C for 6 h to obtain PCN@3DC-2, the negative electrode material.

[0067] Example 3

[0068] This embodiment provides a method for preparing a negative electrode material, comprising the following steps:

[0069] S1: Dissolve 400 mg of anhydrous zinc acetate in 100 mL of DMF by ultrasonication to obtain a zinc salt solution;

[0070] S2: Wash and cut the discarded coke bottle (waste PET) into small pieces, take 4 g of the coke bottle pieces and place them in a zinc salt solution, condense and reflux at 200 °C and stir for 4 h to obtain a reaction solution;

[0071] S3: After the reaction solution was cooled to room temperature, it was placed in a tube furnace under an Ar atmosphere and heated at 10 °C min -1 The heating rate was set at 1200 °C for 2 h to obtain PCN@3DC-3, the negative electrode material.

[0072] Comparative Example 1

[0073] This comparative example provides a method for preparing a negative electrode material, comprising the following steps:

[0074] S1: Dissolve 170 mg of anhydrous zinc acetate in 30 mL of DMF by ultrasonication to obtain a zinc salt solution;

[0075] S2: Wash and cut the discarded coke bottles (waste PET) into small pieces, take 1g of the coke bottle pieces and place them in a zinc salt solution, condense and reflux at 155℃ and stir for 12 h to obtain a reaction solution;

[0076] S3: After the reaction solution was cooled to room temperature, the precipitate was collected by centrifugation, washed several times with deionized water and anhydrous ethanol, and then dried in a vacuum drying oven at 80 °C to obtain a powder product;

[0077] S4: The powder product was placed in a tube furnace under Ar atmosphere at 5 °C min -1 The negative electrode material was obtained by pyrolysis at 900 °C for 6 h at a heating rate of , and was recorded as PC-1.

[0078] Comparative Example 2

[0079] This comparative example provides a method for preparing a negative electrode material, comprising the following steps:

[0080] S1: Wash the discarded coke bottle (waste PET) and cut it into small pieces. Take 1 g of the coke bottle pieces and put them in 30 mL of DMF. Stir under condensation reflux at 155 °C for 12 h to obtain a reaction solution.

[0081] S2: After the reaction solution was cooled to room temperature, it was placed in a tube furnace under an Ar atmosphere at 5 °C min -1 The negative electrode material was obtained by pyrolysis at 900 ℃ for 6 h at a heating rate of , which was recorded as PC-2.

[0082] Comparative Example 3

[0083] This comparative example provides a method for preparing a negative electrode material, comprising the following steps:

[0084] S1: Wash the discarded Coke bottles (waste PET) and cut them into small pieces;

[0085] S2: Take 1g of coke bottle fragments and place them in a tube furnace with Ar atmosphere at 5℃min -1 The negative electrode material was obtained by pyrolysis at 900 ℃ for 6 h at a heating rate of , which was recorded as PC-3.

[0086] The negative electrode materials prepared in the above-mentioned embodiments and comparative examples were tested; wherein, the sodium storage performance of PCN@3DC-1, PCN@3DC-2, PCN@3DC-3 prepared in embodiments 1 to 3, and PC-1, PC-2 and PC-3 prepared in comparative examples 1 to 3 were tested, and the testing method was as follows: the active materials (PCN@3DC-1, PCN@3DC-2, PCN@3DC-3, PC-1, PC-2 and PC-3), conductive carbon black and sodium carboxymethyl cellulose (CMC) were stirred and mixed in a mass ratio of 7:2:1, respectively, with deionized water as solvent to prepare a working electrode. The mixed slurry was coated on a Cu foil and dried under vacuum at 60 °C for 12 h. The mass loading of the active material was about 0.5~1.0 mg. CR 2023 button cells were assembled in a glove box (O2 < 0.01 ppm, H2O < 0.01 ppm) using 1 M sodium hexafluorophosphate (NaPF6) dissolved in ethylene glycol dimethyl ether as the electrolyte, glass fiber purchased from Whatman as the separator, and a sodium sheet with a diameter of 12 mm as the counter electrode. The cells were heated at 0.01–3.00 V (vs Na) using a Land CT 2001 A instrument. + / Na) voltage window for charge and discharge tests.

[0087] Specifically, Figure 1 The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of PCN@3DC-2 prepared in Example 2 are shown in Figure 2. Figure 1 a It can be seen that after high-temperature pyrolysis, a three-dimensional porous structure formed by cross-linking and assembling micron-scale carbon skeleton groups is obtained. The gaps between the carbon skeletons form micron-scale channels. These micropores can provide a buffer space for the volume expansion of the material when sodium ions are embedded and de-embedded. Figure 1 b It can be seen that nanosheets with a thickness of about 8 nm are in situ anchored on the surface of the three-dimensional carbon skeleton. The nanosheets on the surface of the carbon skeleton can provide more active sites for the embedding of sodium ions, which is conducive to the diffusion and transmission of sodium ions and electrons. Figure 1c It can be seen that there are a large number of holes on the surface of the nanosheets, which can not only play a buffering role in the charging and discharging process of the battery, but also help the diffusion of the electrolyte. Figure 1 f It can be seen that the holes on the nanosheets are about 20 nm in size. The formation of these holes may be attributed to the volatilization of zinc metal during the pyrolysis process, which leaves holes in situ on the carbon skeleton and nanosheets.

[0088] Figure 2 The high-resolution transmission electron microscopy (HRTEM) image, the selected area diffraction (SAED) image and the elemental mapping (EDS) image of PCN@3DC-2 prepared in Example 2 are shown in FIG. Figure 2 In a, it can be seen that there is a large amount of amorphous carbon around the holes. Figure 2 b shows that the interlayer spacing of carbon in PCN@3DC-2 is 0.36 nm, corresponding to the (002) crystal plane of carbon. Figure 2 Two diffuse haloes can be clearly seen in c, corresponding to the (002) and (100) crystal planes of carbon. From the EDS image, it can be clearly seen that C, N and O elements are evenly distributed in the carbon skeleton and nanosheets. Since the sublimation point of Zn is 907 °C, there is still some Zn left in PCN@3DC under 900 °C pyrolysis.

[0089] Figure 3 , Figure 4 and Figure 5 The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of PC-1, PC-2 and PC-3 obtained in the preparation process of Comparative Examples 1, 2 and 3 respectively show that compared with PCN@3DC-2, the morphological structures of PC-1, PC-2 and PC-3 all show irregular block shapes, which indicates that the presence of anhydrous zinc acetate and DMF during the pyrolysis process has a crucial influence on the formation of three-dimensional carbon skeleton materials loaded with porous carbon nanosheets.

[0090] Figure 6 The N2 adsorption-desorption isotherms and pore size distribution of PCN@3DC-2 obtained in the preparation process of Example 2 are shown in Figure 2. Figure 6 It can be seen from a that the specific surface area of ​​PCN@3DC-2 is 88.2 m 2 g -1 , and exhibits a typical H3-type hysteresis loop, indicating that the pore structure in PCN@3DC-2 is not very regular. Figure 6 a shows that the average pore size of PCN@3DC-2 is 11.6 nm, indicating that there are a large number of mesopores in PCN@3DC-2. The abundant mesopores are conducive to the diffusion of electrolytes and the rapid transmission of electrons and ions. In addition, there are a certain amount of macropores in the material, indicating that the material is a hierarchical porous structure.

[0091] Figure 7 The Raman spectra, X-ray powder diffraction (XRD) graphs of PCN@3DC-2 prepared in Example 2 and PC-1, PC-2 and PC-3 prepared in Comparative Examples 1 to 3, and the X-ray photoelectron spectroscopy (XPS) graph of PCN@3DC-2 prepared in Example 2 are shown; Figure 7 It can be seen from a that the products after liquid pyrolysis (PCN@3DC-2 and PC-2) have a higher degree of graphitization, while the products after solid pyrolysis (PC-1 and PC-3) have a higher degree of disorder. Figure 7 It can be seen from b that the (002) crystal plane of carbon in the product after liquid pyrolysis is shifted upward, while the (002) crystal plane of carbon in the product after solid pyrolysis is shifted downward, indicating that the product after solid pyrolysis has a larger interlayer spacing. Figure 7 It can be seen from Figure c that after pyrolysis at 900°C, only C, N and O elements can be detected in PCN@3DC-2, but no Zn can be detected, indicating that the Zn content in the material is extremely low, which is consistent with the result that no Zn metal peak was detected in the XRD spectrum of PCN@3DC-2. Figure 7 d It can be seen that the C 1s spectrum of PCN@3DC-2 can be fitted into three carbon peaks, namely CC / C=C at 284.7 eV, CO / CN at 285.42 eV, and C=O at 286.58 eV. Figure 7 It can be seen from the figure that the N 1s spectrum of PCN@3DC-2 can be fitted into three carbon peaks, namely pyridinic N at 398.82 eV, pyrrolic N at 400.89 eV, and graphitic N at 402.94 eV. Figure 7 f It can be seen that the O 1s spectrum of PCN@3DC-2 can be fitted into three carbon peaks, namely C-OH / COC at 531.62 eV, COOH at 532.48 eV, and C=O at 533.72 eV.

[0092] Figure 8 a shows the PCN@3DC-2 electrode at 0.1 mV s -1 From the CV diagram at a scanning rate of , it can be seen that a broad peak appears at 0.8 V in the first cycle, which is due to the formation of the solid electrolyte interface film, while the peak does not appear in the next two cycles, and the CV curves can overlap well, which shows that the PCN@3DC-2 electrode has good reversibility in the sodium storage process. Figure 8 b shows the PCN@3DC-1, PCN@3DC-2, PCN@3DC-3, PC-1, PC-2 and PC-3 electrodes at 0.1 A∙g -1After 90 cycles, the reversible capacities can be maintained at approximately 218.4, 242.1, 226.7, 165.0, 198.3, and 104.7 mAh∙g -1 These results show that compared with PCN@3DC-1, PCN@3DC-3, PC-1, PC-2 and PC-3 electrodes, PCN@3DC-2 electrode has higher discharge specific capacity and long cycle stability. Figure 8 To evaluate the long-term cycling stability of the PCN@3DC-2 electrode at high current density, the PCN@3DC-2 electrode was tested at 1 A∙g -1 After 240 cycles of charge and discharge, the reversible capacity can be maintained at about 231.6 mAh∙g -1 Moreover, it is impressive that the PCN@3DC-2 electrode can -1 After 5000 cycles of charge and discharge tests, it can still provide 171.3 mAh∙g -1 The high reversible specific capacity and the Coulombic efficiency remain close to 100% during cycling. Figure 8 e shows the rate performance of PCN@3DC-1, PCN@3DC-2, PCN@3DC-3, PC-1, PC-2, and PC-3 electrodes at different current densities, among which PCN@3DC-2 electrode exhibits the best performance at 0.1, 0.2, 0.5, 1, 2, 5, 10, 15, 20, 30, and 50 A∙g -1 When the reversible specific capacities of PCN@3DC-2 electrode are 231.4, 208.5, 198.1, 190.4, 180.4, 169.1, 160.5, 147.4, 122.8, 109.2, 99.9, 89.8 and 72.9 mAh g -1 Even at high current densities (50 A∙g -1 ) also showed excellent rate performance. In addition, when the current density was restored to 0.1 A∙g -1 When the temperature of the PCN@3DC-2 electrode was 240 °C, the capacity of the PCN@3DC-2 electrode quickly recovered to 204.4 mAh∙g -1 , and remain stable in subsequent cycles.

[0093] In summary, the excellent sodium storage performance of PCN@3DC-2 electrode may be attributed to the special structure of PCN@3DC-2. The macropores in the hierarchical porous structure of PCN@3DC-2 can provide enough buffer space for the volume expansion of the material when sodium ions are inserted / deinserted, and the mesopores are conducive to the diffusion and transmission of sodium ions and electrons, resulting in excellent rate performance, especially at high current density. In addition, the large specific surface area of ​​the material and the porous carbon nanosheets loaded on the carbon skeleton can provide more active sites for the insertion of sodium ions and facilitate the diffusion of electrolytes, thus showing a high sodium storage capacity.

[0094] The present invention uses discarded cola bottles (PET) as raw materials, condenses and refluxes to dissolve and pyrolyze at high temperature to obtain the target product, a three-dimensional carbon skeleton material (PCN@3DC-2) loaded with porous carbon nanosheets. The process is very simple and the preparation cost is low. Compared with the existing preparation method of hard carbon used for the negative electrode of sodium ion batteries, the present invention not only does not require expensive raw materials, but also the product (PCN@3DC-2) shows more excellent performance in sodium storage, especially at 50A g -1 The synthesis strategy of the present invention provides a new approach for preparing low-cost carbon materials by pyrolysis using waste PET as a precursor and applying them to high-performance negative electrode materials for sodium ion batteries.

[0095] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing a negative electrode material, characterized in that: The steps include: S1: dissolving a zinc salt in an organic solvent to obtain a zinc salt solution; S2: placing the plastic in the zinc salt solution, condensing and refluxing at 80-200° C. to obtain a reaction solution; S3: After cooling the reaction solution to room temperature, placing it in an inert gas atmosphere and pyrolyzing it at 500-1200° C. to obtain a negative electrode material; The plastic is polyethylene terephthalate.

2. The method for preparing the negative electrode material according to claim 1, characterized in that: The plastic is waste polyethylene terephthalate.

3. The method for preparing the negative electrode material according to claim 1 or 2, characterized in that: The zinc salt is selected from at least one of anhydrous zinc acetate, zinc chloride, and zinc nitrate hexahydrate.

4. The method for preparing the negative electrode material according to claim 3, characterized in that: The zinc salt is anhydrous zinc acetate.

5. The method for preparing the negative electrode material according to claim 1 or 2, characterized in that: The organic solvent is selected from at least one of DMF, DMA, DMSO and THF.

6. The method for preparing the negative electrode material according to claim 5, characterized in that: The organic solvent is DMF.

7. The method for preparing the negative electrode material according to claim 1 or 2, characterized in that: The dosage ratio of the zinc salt, the organic solvent and the plastic is (50-400) mg: (10-100) mL: (0.1-4) g.

8. The method for preparing the negative electrode material according to claim 1 or 2, characterized in that: The condensation reflux time in step S2 is 4-20h.

9. The method for preparing the negative electrode material according to claim 1 or 2, characterized in that: The pyrolysis time in step S3 is 2-8h.

10. The method for preparing the negative electrode material according to claim 1 or 2, characterized in that: The pyrolysis rate in step S3 is 2-10 °C min -1 .

11. A negative electrode material, characterized in that: The negative electrode material is prepared by the method for preparing the negative electrode material according to any one of claims 1 to 10.

12. A sodium ion battery, characterized in that: Comprising the negative electrode material as claimed in claim 11.

Citation Information

Patent Citations

  • Method for preparing carbon nanotube by use of biodegradable plastic

    CN102115076A

  • Method for preparing phenolic resin-based foamed activated carbon

    CN107739030A